Chryseobacterium bacteraemia in a patient with heart failure: case report and literature review. Issue 6 (12th November 2020) - Wood, Taylor; Abbate, Antonio; Tchoukina, Inna; Stevens, Michael P
Abstract: Background: A 29-year-old male with recently diagnosed biventricular failure from myopericarditis and subsequent constrictive pericarditis on home milrinone presented to the Emergency Department with fevers/chills. Case summary: On arrival to the Emergency Department, he was found to have septic shock and required vasopressor therapy. Chryseobacterium indologenes grew on his admission blood cultures, and he was treated with ciprofloxacin and piperacillin/tazobactam. He quickly improved, allowing for a successful pericardiectomy, was weaned off inotropes and discharged from the hospital. Discussion: Chryseobacterium indologenes is an environmental Gram-negative rod found in groundwater. It is rarely associated with human infection, but is associated with indwelling lines and has been documented in immunocompromised patients. Treatment typically involves line removal and a fluoroquinolone or piperacillin/tazobactam; the most optimal antimicrobial regimen and duration of treatment are unknown.